2021
DOI: 10.5114/pjp.2021.104659
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HPV16 infection in patients with laryngeal cancer

Abstract: The purpose of the study was to investigate HPV16 infection in laryngeal cancer patients treated with surgery and adjuvant radiotherapy as well as to analyze treatment results in relation to HPV16 infection and selected clinical, histopathological, and radiotherapy parameters. A retrospective analysis was performed in a group of 60 patients with squamous cell carcinoma of the larynx treated surgically and qualified for adjuvant radiotherapy at the Oncology Center in Cracow between 1995 and 2001. The studied gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…The remaining nine articles used descriptive definitions for margin status, such as ‘positive’, ‘microscopically positive’, ‘tumor at the resection surface’, ‘negative’, ‘safe margins’ or ‘no invasive tumor at the resection surface’. These studies reported clear margins in 70–100% and positive margins in 0–30% [ 10 , 11 , 12 , 14 , 16 , 17 , 18 , 19 , 20 ]. The results of our survival data cannot be compared with those in the literature because diverse patient cohorts and descriptive definitions for margin status have been used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining nine articles used descriptive definitions for margin status, such as ‘positive’, ‘microscopically positive’, ‘tumor at the resection surface’, ‘negative’, ‘safe margins’ or ‘no invasive tumor at the resection surface’. These studies reported clear margins in 70–100% and positive margins in 0–30% [ 10 , 11 , 12 , 14 , 16 , 17 , 18 , 19 , 20 ]. The results of our survival data cannot be compared with those in the literature because diverse patient cohorts and descriptive definitions for margin status have been used in different studies.…”
Section: Discussionmentioning
confidence: 99%